Karakteristik Hydrocyclone untuk Pemisahan Minyak dan Air - Dian Ratna Suminar; Nurcahyo Nurcahyo (Jurnal Teknik Kimia dan Lingkungan, 2020)
Eksplorasi minyak bumi dari sumur-sumur yang sudah tua menghasilkan minyak dengan kandungan air tinggi. Hydrocyclone suatu alat yang berfungsi untuk pemisahan cair-cair berdasarkan perbedaan berat jenis setiap komponen. Pemisahan ini terjadi dikarenanakan adanya gaya sentrifugal dan gaya gravitasi yang dihasilkan dari bentuk hydrocyclone yang seperti kerucut. Perancangan dan pembuatan hydrocyclone menghasilkan alat dengan spesifikasi sebagai berikut : diameter pipa masukan : 25,4 mm, diameter cylindrical section : 120 mm, tinggi cylindrical section : 120 mm, tinggi cone section : 600 mm, diameter pipa overflow : 25,4 mm, diameter pipa underflow : 25,4 mm. Laju alir optimum untuk pemisahan air-minyak tanah pada hydrocyclone adalah 91,8 liter/menit dengan kadar minyak tanah di overflow sebesar 11,4% dan kadar minyak tanah di underflow sebesar 3%. Petroleum exploration from old wells produces oil with a very high water content. Hydrocyclone is a device that functions for liquid-liquid separation based on differences in specific gravity of each component. This separation occurs due to the presence of centrifugal forces and gravitational forces resulting from cone-like forms of hydrocyclone. The design and manufacture of hydrocyclone produces tools with the following specifications: input pipe diameter: 25.4 mm, cylindrical section diameter: 120 mm, high cylindrical section: 120 mm, cone section height: 600 mm, overflow pipe diameter: 25.4 mm, underflow pipe diameter: 25.4 mm. The optimum flow rate for the separation of water-kerosene on hydrocyclone is 91.8 liters / minute with the level of kerosene in overflow of 11.4% and the level of kerosene in underflow of 3%.